Modulation of gut microbiota by ab kefir and its effect on endothelial insulin resistance and vascular inflammation in high fat diet-induced obese rats - Babatunde, Mutalub Yahkub (2025)
Obesity significantly increases the risk of cardiovascular and metabolic diseases due to associated insulin resistance. Vascular insulin resistance contributes considerably to the onset of cardiovascular disease which is a primary cause of death among individuals with obesity and metabolic syndrome. Gut microbiota plays a crucial role in maintaining vascular function by influencing metabolic processes and systemic inflammation. Dysbiosis of gut microbiota is commonly observed in obesity and is linked to insulin resistance. Probiotics treatment can effectively modulate intestinal microbiota and kefir probiotics have demonstrated a favourable impact in reducing the risk of several cardiometabolic disorders. AB kefir is an industrially produced multistrain probiotic of lactic acid bacteria and Bifidobacterium. It remains unclear whether AB kefir probiotics can effectively improve obesity associated insulin resistance, inflammation and microbiota dysbiosis. This study aimed to investigate the effects of AB kefir on gut microbiota, body weight, lipid profile, endothelial dysfunction, metabolic and vascular insulin resistance, inflammation and oxidative stress in high-fat diet-induced obese rats. Twenty-four Sprague-Dawley rats were divided into three groups: (i) rats fed normal rat chow, (ii) rats fed a high fat diet (HFD), and (iii) rats fed HFD and gavaged with AB kefir for the last eight weeks of the study. The rats were sacrificed at week 22, body weight and body mass index (BMI) were measured. Blood samples were taken to assess fasting blood glucose and insulin levels. Faecal samples were collected to determine gut microbiota composition using 16S ribosomal RNA sequencing. Aortic tissues were collected for endothelial functional and insulin signalling study as well as Westen blotting to determine the expression of endothelial nitric oxide (eNOS), insulin receptor substrate-1 (IRS-1) and mitogen activated protein kinase (MAPK) protein. Enzyme-linked immunosorbent assay (ELISA) was performed to measure inflammatory and oxidative stress markers. AB kefir treatment in obese rats modulated gut microbiota composition, reduced body weight, improved lipid profiles, improved the impaired acetylcholine- and insulin-mediated relaxation of rat aorta through eNOS/IP3K/IRS-1 pathway, while also reduced inflammation and oxidative stress. Therefore, AB kefir may have the potential to serve as an effective complementary or adjuvant therapy, as well as nutritional approach for the treatment and prevention of cardiometabolic diseases related to obesity.